Post-operative sepsis-induced acute respiratory distress syndrome: risk factors for a life-threatening complication - Bardají-Carrillo, Miguel; Martín-Fernández, Marta; López-Herrero, Rocío; Priede-Vimbela, Juan Manuel; Heredia-Rodríguez, María; Gómez-Sánchez, Esther; Gómez-Pesquera, Estefanía; Lorenzo-López, Mario; Jorge-Monjas, Pablo; Poves-Álvarez, Rodrigo; Villar, Jesús; Tamayo, Eduardo (Frontiers in Medicine, 2024)
Introduction: Prevalence and mortality of the acute respiratory distress syndrome (ARDS) in intensive care units (ICU) are unacceptably high. There is scarce literature on postoperative sepsisinduced ARDS despite that sepsis and major surgery are conditions associated with ARDS. We aimed to examine the impact of postoperative sepsis-induced ARDS on 60-day mortality.We performed a secondary analysis of a prospective observational study in 454 patients who underwent major surgery admitted into a single ICU. Patients were stratified in two groups depending on whether they met criteria for ARDS. Primary outcome was 60-day mortality of postoperative sepsis-induced ARDS. Secondary outcome measures were potential risk factors for postoperative sepsis-induced ARDS, and for 60-day mortality.Results: Higher SOFA score (OR 1.1, 95%CI 1.0-1.3, p=0.020) and higher lactate (OR 1.9, 95%CI 1.2-2.7, p=0.004) at study inclusion were independently associated with ARDS. ARDS patients (n=45) had higher ICU stay (14 [18] vs. 5 [11] days], p<0.001) and longer need for mechanical ventilation (6 [14] vs. 1 [5] days, p<0.001) than non-ARDS patients (n=409). Sixty-day mortality was higher in ARDS patients (OR 2.7, 95%CI 1.1-6.3, p=0.024). Chronic renal failure (OR 4.0, 95%CI 1.2-13.7, p=0.026), elevated lactate dehydrogenase (OR 1.7, 95%CI 1.1-2.7, p=0.015) and higher APACHE II score (OR 2.7, p=0.006) were independently associated with 60-day mortality.Conclusions: Postoperative sepsis-induced ARDS is associated with higher 60-day mortality compared to non-ARDS postoperative septic patients. Postoperative septic patients with higher severity of illness have a greater risk of ARDS and worse outcomes. Further investigation is needed in postoperative sepsis-induced ARDS to prevent ARDS.